2016
DOI: 10.1155/2016/8716257
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Nanodrag Reducer for Low Permeability Reservoir Water Flooding: Long-Chain Alkylamines Modified Graphene Oxide

Abstract: Chemical modification of graphene oxide (GO) by grafting hydrophobic chains on the surface has drawn much attention nowadays in the academic world, and it was suggested that modified GO could lead to new functionalized materials with specific structure and different properties. In this paper, modified GO (M-GO) were synthesized by chemically grafting alkylamines with varying chain lengths on the graphene oxide surface. Successful grafting of alkylamines was confirmed using Fourier transform infrared (FTIR) spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Chen et al investigated the effect of modified GO (M-GO) grafted with alkylamines of different chain lengths on EOR. 36 Hexadecylamine and octadecylamine modified GO reduced the injection pressure and improved the aqueous phase permeability of low permeability reservoirs during water flooding.…”
Section: Applications In Eormentioning
confidence: 99%
“…Chen et al investigated the effect of modified GO (M-GO) grafted with alkylamines of different chain lengths on EOR. 36 Hexadecylamine and octadecylamine modified GO reduced the injection pressure and improved the aqueous phase permeability of low permeability reservoirs during water flooding.…”
Section: Applications In Eormentioning
confidence: 99%
“…Chen et al found that increasing the length of the alkyl chain grafted on GO, increasing the surface roughness of the modified GO, and reducing the surface energy, could increase the contact angle of the surface of hydrophilic core. In addition, the hexadecylamine-and octadecylaminemodified GO have the ability to reduce the water injection pressure and increase the water injection capacity in low-permeability reservoirs (as shown in Figure 4), and can be used as nano-drag reduction agents in low-permeability reservoirs [90]. Khoramian et al studied the oil enhanced recovery capability of GO nanosheets from the perspective of their influence on the viscosity of water phase and emulsification performance.…”
Section: Graphene Oxidementioning
confidence: 99%
“…In recent years, with the reduction of conventional oil and gas resources, the development of low permeability reservoirs has become the focus of oilfield development. , The production costs caused by difficult water injection and high pressure under injection, such as production and operation costs and equipment maintenance costs, are the key problems to be solved. At present, nanomaterials are being developed rapidly and used in the development of oil and gas fields to solve many oil production problems that are difficult to develop in poor oil fields and low permeability reservoirs.…”
Section: Introductionmentioning
confidence: 99%